RETRACTED ARTICLE: Fabrication of anodic aluminum oxide (AAO) nano-porous membrane on both sides of aluminum sheet - Ajab Khan Kasi (2018)
Fabrication of AAO Membrane is a time consuming and sensitive process. Several attempts have made to speed up this process. This paper reports the fabrication of AAO membrane at both sides of aluminum sheet. This method speeds up the fabrication process. This method of fabrication is easier because the aluminum sheet does not need to protect from the back side. This type of fabrication minimizes the total cost of nano-porous membrane. The fabrication of nano-porous membrane has been done by homemade system. The developed system can be used for mild anodization (MA), hard anodization (HA) and electro-polishing. This paper represents the fabrication of AAO membrane using 99.999% pure aluminum and commercial grade impure aluminum. The fabrication was done by MA and HA. © 2010 IEEE.